PSYCHOLOGICAL CHARACTERISTICS OF MUTUAL UNDERSTANDING IN THE RELATIONSHIP OF PARENTS AND CHILDREN (UBS Scientific Bulletin, 2024)
This article discusses the psychological characteristics of mutual understanding in parent-child relationships. Also, in order to study the family situation, parents' attitude towards the personality of the child, experimental work was organized and the results of the research were presented. The article is intended for pedagogues, psychologists, and parents.